2012
DOI: 10.1136/medethics-2012-100770
|View full text |Cite
|
Sign up to set email alerts
|

A legal market in organs: the problem of exploitation

Abstract: The article considers the objection to a commercial market in living donor organs for transplantation on the ground that such a market would be exploitative of the vendors. It examines a key challenge to that objection, to the effect that denying poor people the option to sell an organ is to withhold from them the best that a bad situation has to offer. The article casts serious doubt on this attempt at justifying an organ market, and its philosophical underpinning. Drawing, in part, from the catalogued conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…For quite some time various authors have suggested the introduction of ‘incentives’ [4-6]. The broad spectrum of suggested models ranges from direct cash payments, free market solution or indirect money saving options, here defined as ‘financial incentives’, to incentives that mirror reciprocal non-financial compensation including tokens to express social acknowledgement, bonus points in cases of being on a waiting list, or the coverage of incurred health expenses for the donor.…”
Section: Introductionmentioning
confidence: 99%
“…For quite some time various authors have suggested the introduction of ‘incentives’ [4-6]. The broad spectrum of suggested models ranges from direct cash payments, free market solution or indirect money saving options, here defined as ‘financial incentives’, to incentives that mirror reciprocal non-financial compensation including tokens to express social acknowledgement, bonus points in cases of being on a waiting list, or the coverage of incurred health expenses for the donor.…”
Section: Introductionmentioning
confidence: 99%
“…It may be obvious that bodily integrity is violated if an organ is removed from an individual without his or her consent, but even in a regulated market vendors often face conditions that limit the validity of their consent. As Greasley (2014) writes, it seems clear that poverty contributes to the irrational decision making of kidney vendors. True consent would require freedom from coercion, which is not possible if the basic capabilities of would-be vendors are not secured.…”
Section: Regulated Markets Of Kidneys In Developed Countries or How Tmentioning
confidence: 96%
“…Brewer () and De‐Shalit () are accessible introductions to the connections between exploitation and imperialism, on the one hand, and global justice, on the other. Greasley () offers a cogent summary of the debate on exploitation in commercial organ donation. Structural exploitation is discussed in Zwolinski () and Young ().…”
Section: Further Readingmentioning
confidence: 99%